Nanospace engineering of KOH activated car - Romanos, J. (2011)
This paper demonstrates that nanospace engineering of KOH activated carbon is possible by controlling the degree of carbon consumption and metallic potassium intercalation into the carbon lattice during the activation process. High specific surface areas, porosities, sub-nanometer (<1 nm) and supra-nanometer (1–5 nm) pore volumes are quantitatively controlled by a combination of KOH concentration and activation temperature. The process typically leads to a bimodal pore size distribution, with a large, approximately constant number of sub-nanometer pores and a variable number of supra-nanometer pores. We show how to control the number of supra-nanometer pores in a manner not achieved previously by chemical activation. The chemical mechanism underlying this control is studied by following the evolution of elemental composition, specific surface area, porosity, and pore size distribution during KOH activation and preceding H3PO4 activation. The oxygen, nitrogen, and hydrogen contents decrease during successive activation steps, creating a nanoporous carbon network with a porosity and surface area controllable for various applications, including gas storage. The formation of tunable sub-nanometer and supra-nanometer pores is validated by sub-critical nitrogen adsorption. Surface functional groups of KOH activated carbon are studied by microscopic infrared spectroscopy.